Jiang shan mei ren = An empress and the warriors [videorecording (DVD)] - Cheng, Xiaodong, 1953-; Kou, Zhenhai, 1954-; Ruan, Shisheng; Zhang, Tan, 1966-; Qin, Tiannan, 1949-; Yen, Donnie, 1963-; Guo, Xiaodong, 1974-; Chen, Huilin, 1973-; Lai, Leon, 1966-; Zhao, Xiaoding; Liu, Mark, 1969- (Dragon dynasty (Series), 2009)
Set in ancient China before its unification, during which countless kingdoms battle for supremacy. Yan Feier is thrust onto the throne when her father is killed in battle. Feier and her loyal Murong Xuehu unite to defend the kingdom. But her ambitious cousin Hu Ba sends assassins to kill her. A mysterious hermit Duan Lanquan saves her. Feier falls in love with Duan who offers her another life. With the fate of their kingdom in the balance, Feier must choose between her duty and her dreams.